Uptake, distribution in different tissues, and genotoxicity of imidacloprid in the freshwater fish Australoheros facetus - Iturburu, Fernando Gastón (2017)
The neonicotinoid imidacloprid is under re-evaluation by regulatory agencies because of the poor current information available regarding its potential effects. One of the goals of the present study was to determine imidacloprid uptake and distribution in the freshwater fish Australoheros facetus experimentally exposed for 24 h and 48 h to 100 μg/L, 300 μg/L, and 2500 μg/L. The toxicity of imidacloprid to fish reported in the literature is in the milligrams per liter or gram per liter range, but sublethal effects at micrograms per liter in some groups other than fish have been described. Another goal of the present study was to evaluate imidacloprid's potential genotoxicity and to compare it between the individual compound and a commercial formulation. Concentrations of imidacloprid were measured in water, brain, muscle, gills, gut, liver, and blood by liquid chromatography-tandem mass spectrometry. Imidacloprid was detected in all the tissues tested. Concentrations were higher after 48 h than after 24 h in liver, gills, gut, and muscle, whereas in brain and blood they were similar at both exposure times. Although there was no accumulation, only uptake, of imidacloprid, genotoxicity was observed. In fish exposed to IMIDA NOVA 35®, increased micronucleus frequency at 100 µg/L and 1000 µg/L was detected, whereas in the imidacloprid active ingredient bioassay it increased only at 1000 µg/L imidacloprid. The present findings warn of the possible consequences that fish living in freshwater ecosystems can suffer. Environ Toxicol Chem 2017;36:699–708. © 2016 SETAC.